Ecotoxicological effects of cadmium on the germination and initial development of Schinus terebinthifolius - Silva,Edevaldo da (2017)
Plants can absorb cadmium from contaminated soils. This toxic metal can cause many negative effects on plants morphophysiological development. The aim of this study was to determine the biometric aspects and to assess the ecotoxicological effects of cadmium on the germination and initial development of pepper mastic (Schinus terebinthifolius). The experiment followed a completely randomized design with treatments consisting of eight cadmium concentrations (0.0; 0.2; 0.4; 0.6; 0.8; 1.0; 2.0; 4.0 and 6.0 mM), with four replications. The response variables analyzed included: percentage of germination speed index (GSI), length of shoots and roots of seedlings. Cadmium caused high percentage of inhibition on the germination of S. terebinthifolius, presenting negative effects from 0.2 mM (35.2% inhibition) by 70.2% with 0.6 mM. In early seedling development, it was found that its presence interferes with the root growth more than with shoots. In both parts, cadmium interfered significantly from the concentration of 0.2 mM. However, the 0.4 mM concentration impacts are more pronounced in the root system development. In environments contaminated by cadmium, establishing the germination and development of this species may not be possible.